Beyond the Darkness: Navigating Oguchi Disease with a Singular Case Insight: Doi: 10.36351/pjo.v41i2.2006 - Malik, Hajra Arshad; Abbas, Shehr Bano; Gulzar, Saman; Uzair, Najia (Pakistan Journal of Ophthalmology, 2025)
Oguchi disease represents a hereditary condition characterized by stationary night blindness. It has a characteristic clinical sign, the Mizuo-Nakamura phenomenon. We present a case of a 9-year-old girl who was evaluated for complaints of impaired night vision. Best-corrected visual acuity in both eyes was 20/100. Dilated fundus examination demonstrated a metallic sheen across the retina bilaterally. After a dark adaptation for 2 hours, the characteristic golden-yellow metallic sheen resolved, demonstrating the clinical phenomenon known as the Mizuo-Nakamura effect.